Ikonofilia Francuska semiologia pikturalna i obrazy - Leśniak, Andrzej (Nowa Humanistyka, 2013)
The theoretical weakness of history of art and the cognitive inefficiency of studies on visual culture cause images to remain a challenge for us. Iconophilia is an alternative perspective, within which they are (finally) taken seriously. The history of iconophilia in French humanities (in pictorial semiology in particular) serves the purpose of drafting the proposed future of the thought on images. It is not about a traditional presentation of the history of the notion of an image, but about reflecting on the various strategies of understanding images in the humanities, the effect of which is theory. This study, therefore, relates to the issue of image as a phenomenon, which writes history and theory. (excerpt from a review by Prof. Marta Leśniakowska)